2020
DOI: 10.4103/ijpvm.ijpvm_207_19
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self care management with glycemic control in type 2 diabetic patients

Abstract: Background: The purpose of this study was to investigate the relationship between self-care management and HbA1c level of the patients with type 2 diabetes in YAZD. Methods: This study was a cross-sectional study. The number of 376 diabetic patients referred to the Diabetes Research Center in Yazd entered the study. The data collection tool was a summary of Diabetes Self Care Activity questionnaire (SDSCA), which was collected through interviews with patients. Data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
4
5
3
1
Order By: Relevance
“…This suggested that SCB depended on various factors besides marital status. However, Abate et al [ 36 ] and Modaresi et al [ 37 ] reported significant associations between marital status and SCB, which contradicted our findings. This inconsistency might be due to the differences in the sample characteristics and the proportion of single and married patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This suggested that SCB depended on various factors besides marital status. However, Abate et al [ 36 ] and Modaresi et al [ 37 ] reported significant associations between marital status and SCB, which contradicted our findings. This inconsistency might be due to the differences in the sample characteristics and the proportion of single and married patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Although patients became more experienced and empowered in self-care over time, the chronicity of the disease caused physical and psychological complications and reduced the patient’s adherence to self-care activities. However, Modaresi et al [ 37 ] found a significant association between SCB and duration of disease in diabetic patients, which differed from our findings. This difference might be explained by the shorter duration of disease (< 1 year) and the lower mean age of the participants (2.2 years) in Modaresi’s study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Self-management start from the patients and for the patients, it gives meaningful experience to the patients that would give a positive impact to controlled the diabetes. [ 21 22 ] Those also give positive impact to the healthcare teams that had more self-confidence in supplying patients and families with support and touch. Health care support encourages regular contact and interaction with patients, families, and providers in health care in order to facilitate better management results.…”
Section: Discussionmentioning
confidence: 99%